Prevalence and Associated Risk Factors of Dehydration Among Construction Workers - Rizki, Kartika Sari; Siregar, Santy Deasy; Akasna, Ezra Tri Mutiara; Aulia, Annisa (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Dehydration poses a significant health risk to construction workers due to heavy physical work and exposure to hot working conditions. This study aimed to determine the prevalence of dehydration and identify associated risk factors among construction workers. A cross-section study was conducted involving 32 construction workers in a construction project for the construction of a wheat flour and soybean mill owned by PT. Agri First which operates at KIM 2 Medan. Data were collected using questionnaires, fingertip pulse oximeters, urine refractometers, and observation sheets. Dehydration is categorized based on the level of urine specific gravity (ultrasound). The data was statistically tested using the Fisher Exact test (α=0.05). The majority of workers (75%) were dehydrated. There was no significant relationship between dehydration and age. However, workers with more than 3 years of experience were more likely to be dehydrated compared to workers with less than 3 years of experience (OR = 8,333, 95% CI: 1,392-49,872). Workers with moderate workloads were also more likely to be dehydrated compared to workers with light workloads (OR = 18,333). There was a significant association between water intake and dehydration (p = 0.000). All workers who did not drink enough water were dehydrated, while only 66.7% of those who drank enough water were dehydrated. Workers with more than 3 years of experience, moderate workload, and inadequate water intake have a higher risk of becoming dehydrated. Interventions to improve hydration among construction workers are urgently needed.